Effects of crystal size on methanol to hydrocarbon conversion over single crystals of ZSM-5 studied by synchrotron infrared microspectroscopy. Issue 34 (16th March 2020) - Minova, Ivalina B.; Matam, Santhosh K.; Greenaway, Alex; Catlow, C. Richard A.; Frogley, Mark D.; Cinque, Gianfelice; Wright, Paul A.; Howe, Russell F.
Abstract : The induction period for alkene formation from methanol in single crystals of HZSM-5 decreases with decreasing crystal size and increasing temperature and hydrocarbon pool species are formed almost instantaneously at higher temperatures. Abstract : Operando synchrotron infrared microspectroscopy (OIMS) was used to study the conversion of methanol over coffin-shaped HZSM-5 crystals of different sizes: large (∼250 × 80 × 85 μm 3 ), medium (∼160 × 60 × 60 μm 3 ) and small (∼55 × 30 × 30 μm 3 ). The induction period, for direct alkene formation by deprotonation of surface methoxy groups, was found to decrease with decreasing crystal size and with increasing reaction temperature. Experiments with a continuous flow of dimethylether showed that evolution of the hydrocarbon pool and indirect alkene formation is also strongly dependent on crystal size. These measurements suggest that the hydrocarbon pool formation and indirect alkene generation should be almost instantaneous at reaction temperatures used in practical catalysis with crystal sizes typically ∼1 μm 3 .